2021
DOI: 10.9745/ghsp-d-20-00641
|View full text |Cite
|
Sign up to set email alerts
|

Faith-Based Advocacy for Family Planning Works: Evidence From Kenya and Zambia

Abstract: Although it is often assumed that religion has a negative influence on family planning (FP), virtually all faith traditions support the concept of healthy timing and spacing of pregnancy. n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Therefore, health promotion interventions that use a social network approach that relies on collaboration between public health organizations and community “links” or gatekeepers can be effective in disseminating information and adoption of preventive behaviors (Kincaid, 2000 ). This approach has been effective in promoting the importance of family planning and increasing the contraceptive use uptake globally, by training community links on how to facilitate discussions to clarify any misconceptions and share their adoption of modern contraceptive use (Bormet et al, 2021 ; Kincaid, 2000 ; Lowe & Moore, 2014 ). These community links are usually individuals within organizations already embedded in the communities and collaborating with them can help reach a wide range of community members, especially hard to reach and at risk populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, health promotion interventions that use a social network approach that relies on collaboration between public health organizations and community “links” or gatekeepers can be effective in disseminating information and adoption of preventive behaviors (Kincaid, 2000 ). This approach has been effective in promoting the importance of family planning and increasing the contraceptive use uptake globally, by training community links on how to facilitate discussions to clarify any misconceptions and share their adoption of modern contraceptive use (Bormet et al, 2021 ; Kincaid, 2000 ; Lowe & Moore, 2014 ). These community links are usually individuals within organizations already embedded in the communities and collaborating with them can help reach a wide range of community members, especially hard to reach and at risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…These community links are usually individuals within organizations already embedded in the communities and collaborating with them can help reach a wide range of community members, especially hard to reach and at risk populations. To illustrate, Borment et al (2021) found that contraceptive uptake was found to be 1.7 times higher for women exposed to family planning messages from religious leaders than those that were not (Bormet et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was also increased sensitization and investment to promote family planning, birth spacing, and manageable families [26,27], including committing to the FP2020 goals [28].…”
Section: Discussionmentioning
confidence: 99%
“…Faith leaders have shown they can be effective advocates not only for HTSP within their own faith communities, but also for better policies, increased resources, and access to voluntary FP services [7]. In sub-Saharan Africa (SSA) FP uptake can be accelerated through the extensive faith-based networks that own and operate 20-50% of health care facilities in many SSA countries [7][8][9].…”
Section: Douglas Hubermentioning
confidence: 99%
“…Faith leaders have shown they can be effective advocates not only for HTSP within their own faith communities, but also for better policies, increased resources, and access to voluntary FP services [7]. In sub-Saharan Africa (SSA) FP uptake can be accelerated through the extensive faith-based networks that own and operate 20-50% of health care facilities in many SSA countries [7][8][9]. Three pillars have provided a solid base for HTSP/FP results: 1) engaging faith leaders to recognize the value of HTSP and voluntary FP and to advocate for the same; 2) training, equipping, and supplying faith-based health facilities; and 3) utilizing community health workers (CHWs) to deliver community-based contraceptives and refer for clinic-based methods.…”
Section: Douglas Hubermentioning
confidence: 99%